African American Cultural History Relative to Blues Music and Its Origins in Paxico, KS, 1890-1930 - Saenger, Allana (Kansas State University. Dept. of History. Chapman Center for Rural Studies, 2010)
Allana Saenger finds connections between the modern day Paxico Blues Festival and the African American population of early Wabaunsee County. She describes the tradition of church singing in black congregations with vivid a capella hymns and homemade tambourines. Interviews with blues festival organizer Marlene McKeithen highlight the family connections to this early black settlement and establish that many Kansas City blues musicians come from families in the Paxico-Newbury area.
Keywords: African American; Wabaunsee County; Paxico; Blues